DAMPAK PEMBANGUNAN BANDARA HALU OLEO TERHADAP PERUBAHAN KESEJAHTERAAN MASYARAKAT DI DESA AMBAIPUA KECAMATAN RANOMEETO KABUPATEN KONAWE SELATAN - Dewantara, Sulkifli Ananda; Kasim, Syaifuddin S.; Sarmadan, Sarmadan (Universitas Halu Oleo, 2022)
This study aims to determine the impact of airport construction on socio-economic and territorial changes in the community in Ambaipua village, Ranomeeto sub-district, South Konawe district. This type of research is descriptive qualitative, one type of research whose aim is to present a complete picture of the social setting or is intended for exploration and clarification of a phenomenon or social reality, by describing those with regard to the problem and the unit under study between the phenomena being tested. Meanwhile, the informants in this study are the people of Ambaipua Village who work at Halu Oleo Airport and the people of Ambaipua Village around Halu Oleo Airport.The results showed that: 1) Social impact: Increased population mobility, Improvement of community social networks, Social Interaction. 2) Economic Impact: Increase in negotiations and trade agreements, Shipping of trade goods. 3) Territorial Impact: Creating new jobs for the community, Increasing community income, Creating healthy price stability.